2013
DOI: 10.3109/07420528.2012.754455
|View full text |Cite
|
Sign up to set email alerts
|

Human Chronotype Is Determined in Bodily Cells Under Real-Life Conditions

Abstract: Individuals differ in their preferred timing of sleep and activity, which is referred to as a chronotype. The timing shows a wide distribution; extremely early chronotypes may wake up when the extremely late chronotypes fall asleep. The chronotype is supposed to be determined by the central circadian clock located in the suprachiasmatic nuclei (SCN) of the hypothalamus because the phasing of the pineal melatonin rhythm, which is driven by the SCN, correlates with the sleep timing preference. In addition to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 47 publications
(61 reference statements)
2
30
0
1
Order By: Relevance
“…CLOCK gene variants alter circadian amplitude and phase (55, 56), biomarkers also associated with morning-evening variation in chronotypes (57), suggesting that such gene mutations might mediate rapid antidepressant response to ketamine (Table 3), and that their markers (amplitude and phase) may also be useful for predicting ketamine response per se .…”
Section: Discussionmentioning
confidence: 99%
“…CLOCK gene variants alter circadian amplitude and phase (55, 56), biomarkers also associated with morning-evening variation in chronotypes (57), suggesting that such gene mutations might mediate rapid antidepressant response to ketamine (Table 3), and that their markers (amplitude and phase) may also be useful for predicting ketamine response per se .…”
Section: Discussionmentioning
confidence: 99%
“…LD 12∶12) are phase advanced in comparison to that of wild type animals, while oppositely, these peripheral clocks are phase delayed in long period Cry2 -/- mice in a tissue specific manner. The resulting dissonance between body time and environmental time likely mimics the condition encountered by human “larks” and “owls”, whose morningness and eveningness chronotype has been associated with alterations in the period and phase of their molecular circadian oscillator [46], [47]. Recent studies indicate that indeed the physiological period length of the human clock in vivo correlates with the period of the peripheral molecular oscillator in cultured fibroblasts from the same individuals [24], [25], [48].…”
Section: Discussionmentioning
confidence: 95%
“…These temperature rhythms have been shown to correlate with changes in dim light melatonin onset, a standard for determining circadian phase in people (Nováková et al, 2013). Despite the aforementioned studies, assessment of wrist temperature rhythms in healthy college age men with variable sleep/wake/activity schedules has not been performed.…”
Section: Resultsmentioning
confidence: 99%
“…Early studies using this approach validated it against dim light melatonin measures and found that the rise in wrist temperature occurred in anticipation of the evening increase in melatonin. Decreases in activity, changes in body position and increases in declared sleep propensity were delayed with respect to increases in dim light melatonin (Bonmati-Carrion et al, 2014; Corbalán-Tutau et al, 2011; Gompper et al, 2010; Kripke et al, 2005; Morgan et al, 1998; Nováková et al, 2013; Sarabia et al, 2008; van Marken Lichtenbelt et al, 2006). Furthermore, wrist skin temperature measures have been reported to be inversely correlated and phase-advanced with the oscillations of core body temperature, thus making this non-intrusive measurement method a reliable candidate to examine circadian rhythmicity (Marotte & Timbal, 1981; Sarabia et al, 2008).…”
Section: Introductionmentioning
confidence: 98%